Introducing the dry law in the Kazan governorate during the World War I - S.N. Blinjaev; O.N. Shirokov (Ученые записки Казанского университета: Серия Гуманитарные науки)
Based on the archival materials of fund no. 82 of the State Historical Archive of the Chuvash Republic, the prerequisites for introduction, implementation, and consequences of the dry law during the mobilization in the course of the World War I have been studied. The problem under our consideration is highly relevant, because the dry law seriously influenced the social and financial aspects of life during the war period. The novelty of the research is that there are no scientific publications or materials in the regional historiography where the problem is considered in this perspective. We have carried out a review of the studies performed by Soviet, Russian, including the regional ones, historiographers, as well as of the archival sources. The policy of local authorities on implementation of the dry law and other direction of the state powers, its consequences in the context of the historical events that took place in the Russian Empire have been analyzed. The obtained results allowed us to make the following conclusions: the well-developed anti-alcohol movement and the adopted orders and circulars have made it possible to introduce the dry law in the entire territory of the Kazan governorate and Chuvashia, particularly during the period of mobilization, and its implementation was accompanied by rather gentle measures for alcohol prohibition.